Using motion capture technology to measure the effects of magnification loupes on dental operator posture: A pilot study - Branson, B G; Abnos, R M; Simmer-Beck, M L; King, G W; Siddicky, S F (Work (Reading, Mass.), 2018)
Motion analysis has great potential for quantitatively evaluating dental operator posture and the impact of interventions such as magnification loupes on posture and subsequent development of musculoskeletal disorders. This study sought to determine the feasibility of motion capture technology for measurement of dental operator posture and examine the impact that different styles of magnification loupes had on dental operator posture. Forward and lateral head flexion were measured for two different operators while completing a periodontal probing procedure. Each was measured while wearing magnification loupes (flip up-FL and through the lens-TTL) and basic safety lenses. Operators both exhibited reduced forward flexion range of motion (ROM) when using loupes (TTL or FL) compared to a baseline lens (BL). In contrast to forward flexion, no consistent trends were observed for lateral flexion between subjects. The researchers can report that it is possible to measure dental operator posture using motion capture technology. More study is needed to determine which type of magnification loupes (FL or TTL) are superior in improving dental operator posture. Some evidence was found supporting that the quality of operator posture may more likely be related to the use of magnification loupes, rather than the specific type of lenses worn.